Buddhist poetry and colonialism: Alagiyavanna and the Portuguese in Sri Lanka - Berkwitz, Stephen C. (Oxford University Press, 2013)
This title examines five works by the poet Alagiyavanna to demonstrate how Buddhism in Sri Lanka was transformed by the encounters with Portuguese colonialism in the 16th and 17th centuries.